Teachers Who are Stuck in Time: Development and Validation of Teachers’ Time Poverty Scale - Liu T; Yang X; Meng F; Wang Q (Psychology Research and Behavior Management, 2023)
Tianyu Liu,1,* Xiantong Yang,2,* Fanhua Meng,1 Qiang Wang1 1College of Elementary Education and College of Education, Capital Normal University, Beijing, People’s Republic of China; 2Faculty of Psychology, Beijing Normal University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiang Wang, College of Elementary Education and College of Education, Capital Normal University, 105 West 3rd Ring North Road, Beijing, People’s Republic of China, Tel +86 13811227118, Email qwchem@gmail.comPurpose: Time poverty has been shown to adversely affect individuals’ development as well as organizations and countries, which is also a widespread problem among teachers, affecting work performance, mental health, and even the development of students and schools. However, the advancement of education research on time poverty has been stymied by the lack of a validated measure. Therefore, to fill the theoretical gap of time poverty in education and to compensate for the absence of an instrument for measuring teachers’ time poverty and the challenges of using objective measures, it is necessary to develop and verify a domain-specific measurement instrument among teachers.Patients and Methods: An online questionnaire is designed through a Chinese data collection platform (Questionnaire Star). Study 1 and Study 2 are a cross-sectional study included 713 teachers in China and the descriptive statistics, correlation analysis and analyses of exploratory and confirmatory factors are used to develop the Teachers’ Time Poverty Scale. Study 3 and Study 4 are a longitudinal study included 330 teachers, while the Time Confusion Tendency Scale and Life Satisfaction Scale is used to verify the measurement tool. SPSS 26.0 and Mplus 8.3 are used to analyze the data.Results: Teachers’ Time Poverty Scale with the single-factor structure exhibits good psychometric properties based on seven items. And teachers’ time poverty can negatively and significantly predict life satisfaction and teachers’ time poverty can be positively and significantly predicted by time confusion tendency.Conclusion: Teachers’ Time Poverty Scale is a useful tool that can be used in actual investigations to provide empirical support for teachers, schools, and education policy makers.Keywords: teachers, time poverty, scale development, scale validation, time confusion tendency, life satisfaction